Upgrading Pembuatan Laporan Keuangan dengan Sistem Enterprise Service Bus pada Seven Retail Group - Dodik Maiwan; Amelia Anwar (Universitas Kristen Indonesia Toraja, 2024)
Potential weaknesses faced by the company. So it is necessary to consider the aspects of process inefficiency, risk of work errors, delays in information, lack of transparency, high operational costs, vulnerability to data loss and difficulties in monitoring performance. In the current era of globalization and digitization, companies face pressure to increase operational efficiency and accountability in presenting financial information. By using the PALS (Pasticipatory Action Learning System) method, where this method basically involves accounting staff in the process of upgrading the Enterprise Service Bus (ESB) system from 30 accounting staff and 5 staff will be taken for the interview sample in this research. From the problems currently faced by companies in managing financial reports, they have not been able to carry out systematic recording. With better data integration using ESB, a company's various systems and applications can be connected and communicate well. In real-time reporting compared to manual (conventional) recording which requires processing time, ESB allows for better real-time financial reports.